2018
DOI: 10.17265/1539-8072/2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Learning Environment on Learner Autonomy: A comparative Study of Polish and Yemeni EFL Undergraduate Learners

Abstract: The goal of autonomous language learning is to create an atmosphere where learners take charge of their own learning. Creating this atmosphere encounters various challenges which are partially context-specific. Influenced by the learning environment, learners of different educational contexts vary in their degree of autonomy. The present study examines the impact of the learning environment on learner autonomy at higher education. The study focuses on the differences between Polish and Yemeni EFL (English as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…As Teng (2019) notes, theoretical discussions around LA are far from coherent, consistent or systematic. Many scholars use LA synonymously with autonomous learning (Kyu, 2018;Thanh, 2019;Yu, 2020;Zaidi et al, 2020), learner independence (Kim & Yoon, 2021;Zaidi et al, 2020), independent learning, self-directed learning or self-direction (Al-Khawlani, 2018;Gulyamova & Kadirova, 2021;Hawkins, 2018), learner-centredness (Kyu, 2018;Yu, 2020), learner self-regulation (Hawkins, 2018;Oxana et al, 2020) and self-managed learning (Marsevani, 2021). It is a difficult and complex concept to define precisely (Gulyamova & Kadirova, 2021;Kim & Yoon, 2021;Sereti & Giossos, 2018;Teng, 2019), because of its broad and abstract nature (Oxana et al, 2020).…”
Section: Conceptualising Learner Autonomymentioning
confidence: 99%
“…As Teng (2019) notes, theoretical discussions around LA are far from coherent, consistent or systematic. Many scholars use LA synonymously with autonomous learning (Kyu, 2018;Thanh, 2019;Yu, 2020;Zaidi et al, 2020), learner independence (Kim & Yoon, 2021;Zaidi et al, 2020), independent learning, self-directed learning or self-direction (Al-Khawlani, 2018;Gulyamova & Kadirova, 2021;Hawkins, 2018), learner-centredness (Kyu, 2018;Yu, 2020), learner self-regulation (Hawkins, 2018;Oxana et al, 2020) and self-managed learning (Marsevani, 2021). It is a difficult and complex concept to define precisely (Gulyamova & Kadirova, 2021;Kim & Yoon, 2021;Sereti & Giossos, 2018;Teng, 2019), because of its broad and abstract nature (Oxana et al, 2020).…”
Section: Conceptualising Learner Autonomymentioning
confidence: 99%
“…According to Al-Khawlani (2018), "To cope with the highly modern, progressive, and global learning environments, we need to consistently develop and improve skills and abilities of the learners as well as learning styles" (p. 109). For upgrading overall knowledge of EFL with full content knowledge in the EFL contexts, teachers need to teach innovative skills and learners need to be autonomous learners.…”
Section: Third Semester As the Turning Point Of My Efl Learningmentioning
confidence: 99%
“…So far I consulted the previous research studies regarding learner autonomy in various EFL contexts done by Al-Khawlani (2018), Almusharraf (2018), Bozkurt and Arslan (2018), Godwin-Jones (2019), Jora (2020), Negi (2019), Panta (2019) and Yuzulia (2020). Among these research studies, Al-Khawlani's (2018) study revealed that there was a significant difference between Polish and Yemeni learners in some of the learning categories.…”
Section: Introductionmentioning
confidence: 99%